Performance of bond strength between ultra-high-performance concrete and concrete substrates (concrete screed and self-compacted concrete): An experimental study. (1st July 2022) - Al-Osta, Mohammed A.; Ahmad, Shamsad; Al-Madani, Mohammed K.; Khalid, Hammad R.; Al-Huri, Mohammed; Al-Fakih, Amin
Abstract: Ultra-high-performance concrete (UHPC) is one of the contemporary overlay materials for repairing and retrofitting of reinforced concrete (RC) members. It possesses excellent compressive and tensile strength, as well as long durability. Nevertheless, the bonding performance between the overlay interface (UHPC) and the substrate concrete must be adequate under various loading, curing, and exposure circumstances. Therefore, this research examined, experimentally, the interfacial bonding behavior of UHPC overlay and two distinct substrates, namely concrete screed (CS) and self-compacted concrete (SCC). Four parameters impacting bond strength behavior, including three different substrate surface preparations, curing conditions, exposure environments, and testing techniques, were used to fulfill the goal of this study. The tests findings revealed that the substrate surface preparation and the exposure conditions had significant effects on the bond behavior of both UHPC-SC and UHPC-SCC while curing conditions seemed not to have any significant effects. The highest bond strength was obtained for specimens having sandblasted substrate preparation technique regardless of the bond test method. However, specimens tested under the bi-surface shear strength technique exhibited high bonding strength with the drill holes substrate preparation technique due to the presence of drilled holes that were being filled with UHPC. The splitting tensile test is a reliable test technique to examine the impact of repeated cyclic exposure samples. As a result of this, a substantial reduction in bond strength of nearly 32%, 55%, and 26% of the UHPC-SCC and 31.84%, 51.5%, and 41.42% for UHPC-SC interfaces for as-cast (AC), drilling hole (DH), and sandblasting (SB) substrate surface preparations, respectively, were obtained. ANOVA was carried out and found to be aligned with the experimental findings. Highlights: The effect of different bond tests and surface preparation on bonding strength was investigated. The splitting tensile test was the reliable test method to examine the impact of repeated cyclic exposure. Sandblasting preparation technique yielded the strongest bond strength in all bonding tests. Curing condition showed no effects on the bond strengths of UHPC-SCC and UHPC-SC composites.